The effect of sertraline-selenium combination on cardiac contractile strength - Solak, Hatice; Solak Görmüş, Z. Işık; Özen Koca, Raviye; Akkuş, Merve; Görmüş, Niyazi (The European Research Journal, 2025)
Objectives: Individuals with myocardial infarction (MI) frequently exhibit a heightened prevalence of depression, which elevates the likelihood of negative cardiovascular outcomes. This study aimed to assess the potential synergistic effects of sertraline, an antidepressant utilised for the prevention and treatment of depression commonly associated with cardiac disorders, and selenium, an antioxidant trace element, on atrial contraction force. Methods: Thirty-two adult male Wistar albino rats were randomly allocated into four groups. Atrial strips were positioned in the organ bath, and the tension was calibrated to 2 g. In the control group, isometric contractions were elicited using 10-3 M adrenaline, and the contractions were documented. Sertraline (S) was incrementally administered to the S group in dosages of 0.01 mM, 0.1 mM, 1 mM, and 2 mM. In the Selenium (Se) Group, selenium was incrementally administered at concentrations of 0.1, 1, 2, and 4 mmol/L. S+Se group, S cumulative (0.01 mM, 0.1 mM, 1 mM, 2 mM) and Se cumulative (0.1, 1, 2, 4) mmol/L were administered at fifteen-minute intervals. Results: The S group had a statistically significant reduction in contraction compared to the control group. Statistically substantial inhibition was noted in the Se group relative to the control group. Statistically significant contraction inhibition was noted in the S+Se group relative to the S group and Se group (P=0.035 and P=0.02, respectively). Conclusions: According to the results of our study, sertraline-selenium combination showed an effect by inhibition of cardiac Ca2+ channels in rat atrium. Additional research is needed to elucidate the mechanism of action of sertraline, which is used in the treatment of depression that often accompanies cardiac disorders, and selenium, an effective trace element with antioxidant properties.